Trigeminal neuralgia caused by cavernoma: A case report with literature review - Liu, Hongyu; Chen, Chuanbiao; Liu, Yuyang; Liu, Jialin; Yu, Xinguang; Chen, Ling (Frontiers in Neurology, 2022)
Cavernoma is the second most common cerebrovascular lesion. Cavernoma involving the cranial nerves is very rare. Only 15 cases of cavernoma presenting with trigeminal neuralgia (TN) have been previously reported. Here, we report a rare case of cavernoma manifesting with TN. A young female patient with a 15-day history of right-sided lancinating pain in the face, difficulty in opening the mouth, and hearing dysesthesia. Magnetic resonance imaging (MRI) revealed a well-demarcated lesion in the cerebellopontine angle related closely to the root of the trigeminal nerve. The initial impression was that of a neurinoma. The lesion was surgically resected via the retrosigmoid approach, postoperative pathological analysis confirmed the diagnosis of cavernoma, and the patient's pain and difficulty in opening the mouth resolved completely. We presented the 16th documented case of cavernoma with TN. Although cavernoma involving the trigeminal nerve is extremely rare, this diagnosis should be taken into consideration when a lesion in the cerebellopontine angle is detected on MRI, and the clinical manifestation is consistent with that of secondary TN. Specialized MRI sequences, such as susceptibility weighted imaging (SWI), gradient echo T2, and constructive interference in steady-state (CISS)-weighted imaging, aid in establishing the diagnosis. Resection via craniotomy may be the primary management strategy for cavernoma causing TN. In addition, gamma knife radiosurgery (GKRS) and percutaneous balloon compression (PBC) may ameliorate the pain to some extent.